Glutaminolysis: A Driver of Vascular and Cardiac Remodeling in Pulmonary Arterial Hypertension - Mprah, Richard; Adzika, Gabriel Komla; Gyasi, Yusif I.; Ndzie Noah, Marie Louise; Adu-Amankwaah, Joseph; Adekunle, Adebayo O.; Duah, Maxwell; Wowui, Prosperl Ivette; Weili, Qiao (Frontiers in Cardiovascular Medicine, 2021)
Pulmonary arterial hypertension (PAH) is a decimating ailment described by chronic precapillary pulmonary hypertension, an elevated mean pulmonary arterial pressure with a normal pulmonary capillary wedge pressure, and a raised pulmonary vascular resistance resulting in increased right ventricular afterload culminating in heart failure and death. Current PAH treatments regulate the vasodilatory/vasoconstrictory balance of pulmonary vessels. However, these treatment options are unable to stop the progression of, or reverse an already established disease. Recent studies have advanced a metabolic dysregulation, featuring increased glutamine metabolism, as a mechanism driving PAH progression. Metabolic dysregulation in PAH leads to increased glutaminolysis to produce substrate to meet the high energy requirement by hyperproliferative and apoptosis-resistant pulmonary vascular cells (PVCs). This paper explores the role of glutamate metabolism in PAH and how it could be targeted as an anti-vascular remodelling therapeutic strategy.